1997
DOI: 10.2134/jeq1997.00472425002600060008x
|View full text |Cite
|
Sign up to set email alerts
|

Time Dependency of Triticonazole Fungicide Sorption and Consequences for Diffusion in Soil

Abstract: Diffusion is a key process regarding the redistribution in soils of systemic pesticides applied in seed treatments. We investigated the influence of nonequilibrium sorption on the diffusivity of triticonazole fungicide [(1RS)‐(E)‐5‐(4‐chlorophenyl‐methylen)‐2,2‐dimethyl‐1‐(1H‐1,2,4‐triazol‐1‐ylmethyl)‐cyclopentan‐1‐ol] in loam clay soil from Grignon, France (Typic Eutrochrept). Triticonazole diffusion coefficients were measured in saturated soil columns for time periods ranging from 1 to 25 d. Nonequilibrium s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 0 publications
3
18
0
Order By: Relevance
“…Instead, under optimal conditions of soil microbial activity (28 °C; 90% field capacity), triticonazole mineralization in soil is small (<1%), indicating high stability of the molecule and little cleavage of the benzyl radiolabelled ring. This accords with previous studies showing triazole fungicides to be very stable in soil,20 and indicating slow and linear triticonazole mineralization 9, 12. HPLC analysis (data not shown) revealed that the extractable radioactivity of all the samples mainly consisted of the parent content (>80%).…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Instead, under optimal conditions of soil microbial activity (28 °C; 90% field capacity), triticonazole mineralization in soil is small (<1%), indicating high stability of the molecule and little cleavage of the benzyl radiolabelled ring. This accords with previous studies showing triazole fungicides to be very stable in soil,20 and indicating slow and linear triticonazole mineralization 9, 12. HPLC analysis (data not shown) revealed that the extractable radioactivity of all the samples mainly consisted of the parent content (>80%).…”
Section: Resultssupporting
confidence: 91%
“…After seven days of incubation, non‐extractable residues in soils were between 3 and 8% of initial radioactivity (Table 4). Previous experiments have also shown similar amounts of bound residues immediately after treatment 12. Bound residues may arise from physical trapping in the internal voids of soil organic matter 18, 19.…”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…[27,30] Diffusion is one of the main mechanisms involved in the formation of bound residues of pesticides in soil. [27,30] Diffusion is one of the main mechanisms involved in the formation of bound residues of pesticides in soil.…”
Section: Reprintsmentioning
confidence: 99%
“…Beigel et al (1997) demonstrated that the diffusion and sorption coefficients of the fungicide triticonazole in soil was time dependent, which enabled them to predict the temporal variation of triticonazole concentration in soils. Jamet and Eudeline (1992) compared the mobility of 17 triazole fungicides in a silt loam soil and concluded that their mobility was inversely related to their octanol/water partition coefficient.…”
Section: Introductionmentioning
confidence: 99%